2019
DOI: 10.1080/21645515.2019.1651141
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of the therapeutic vaccine TG1050 in chronic hepatitis B patients: a phase 1b placebo-controlled trial

Abstract: Treatment of chronic hepatitis B (CHB) typically requires lifelong administration of drugs. Cohort and preclinical studies have established the link between a functional T-cell-mounted immunity and resolution of infection. TG1050 is an adenovirus 5-based vaccine that expresses HBV polymerase and domains of core and surface antigen and has shown immunogenicity and antiviral effects in mice. We performed a phase 1 clinical trial to assess safety and explore immunogenicity and early efficacy of TG1050 in CHB pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 43 publications
2
37
0
3
Order By: Relevance
“…A non-replicative adenoviral vector harboring HBsAg, HBcAg, and Polymerase (TG1050) was shown to induce strong HBV multi-specific and prolonged T-cell responses in the mouse model (145). A Phase Ib study was performed in CHB patients and demonstrated the safety and immunogenicity of TG1050, supporting future testing in combination with antivirals (146).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…A non-replicative adenoviral vector harboring HBsAg, HBcAg, and Polymerase (TG1050) was shown to induce strong HBV multi-specific and prolonged T-cell responses in the mouse model (145). A Phase Ib study was performed in CHB patients and demonstrated the safety and immunogenicity of TG1050, supporting future testing in combination with antivirals (146).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…The three doses used were 10 9 , 10 10 , 10 11 virus particles of TG1050. All doses were well tolerated in both cohorts and the vaccine was capable of inducing IFN-γ producing T cells that targeted one to three encoded antigens, more so with the 10 10 virus particle dose [ 110 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Among the vectored vaccines, TG1050 has completed Phase Ib trial. 95 TG1050 is an adenovirus serotype 5 vectored vaccine encoding truncated HBV core, a modified HBV DNA polymerase and two HBV envelope domains. IFN-γ producing HBVspecific T cells were produced, but only minor decreases in Figure 13.…”
Section: Discussionmentioning
confidence: 99%